2014
DOI: 10.1111/gcb.12769
|View full text |Cite
|
Sign up to set email alerts
|

Response of wheat restricted‐tillering and vigorous growth traits to variables of climate change

Abstract: The response of wheat to the variables of climate change includes elevated CO2, high temperature, and drought which vary according to the levels of each variable and genotype. Independently, elevated CO2, high temperature, and terminal drought affect wheat biomass and grain yield, but the interactive effects of these three variables are not well known. The aim of this study was to determine the effects of elevated CO2 when combined with high temperature and terminal drought on the high-yielding traits of restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…There was no difference in grain yield between the two sister lines contrasting in tillering under any treatment, despite the presence of more tillers in the free-tillering line under elevated CO 2 . Although tillering in the restricted-tillering line was not affected by elevated CO 2 or high temperature, leaf extension, and leaf area do respond to elevations in CO 2 ( Dias de Oliveira et al, 2015 ) as well as leaf photosynthetic rates. Therefore, total canopy photosynthesis was probably similar between both lines.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…There was no difference in grain yield between the two sister lines contrasting in tillering under any treatment, despite the presence of more tillers in the free-tillering line under elevated CO 2 . Although tillering in the restricted-tillering line was not affected by elevated CO 2 or high temperature, leaf extension, and leaf area do respond to elevations in CO 2 ( Dias de Oliveira et al, 2015 ) as well as leaf photosynthetic rates. Therefore, total canopy photosynthesis was probably similar between both lines.…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study, grain yield in a free-tillering wheat line, with the potential to increase sink capacity, did not differ from its isogenic restricted-tillering line, with lower sink capacity. This was because the free-tillering line increased grain number per unit area due to elevated CO 2 , but had smaller grains ( Dias de Oliveira et al, 2015 ), presumably due to the negative correlation between grain number per unit area and grain size ( Grafius, 1972 ). Increasing grain number in wheat is considered critical for improving grain yield ( Fischer and Aguilar, 1976 ; Fischer, 1985 , 2011 ), but it is also likely that grain yield improvement may be limited by grain size ( Grafius, 1972 ; Rajaram and Ginkel, 1996 ; Acreche and Slafer, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into grass architecture using phylogenetic and genomic methods has shown similarities between different cereal crops, with the tendency for crops to have taller, straighter growth and apical dominance, in contrast to their wild relatives (Doust, 2007;Fuller et al, 2010). Improvements to tiller economy are currently underway in modern crop breeding, with particular interest in the tin gene in wheat, which when manipulated, produces plants with fewer tillers, larger spikes and more seeds than wildtype in drought and elevated CO 2 conditions (Dias de Oliveira, Siddique, Bramley, Stefanova, & Palta, 2015;Mitchell, Rebetzke, Chapman, & Fukai, 2013;Tausz-Posch et al, 2015).…”
Section: Changes In Tillering Under Competitionmentioning
confidence: 99%
“…In our study, changes in the plant growth time, such as shortening of the tillering stage would result in reduction of production. Moreover, if elevated temperatures happen during the time from heading stage to maturing stage, the heat stress can decrease post‐heading duration and grain yield, because there is also a significant positive correlation of post‐heading duration with tillers and grain number density . Elevated temperature may also impact grain quality, such as wet gluten, nitrogen, and soluble sugar, because leaf expansion, photosynthesis and grain filling are key temperature dependent physiological processes .…”
Section: Discussionmentioning
confidence: 99%